Integrated untargeted fecal metabolomics and gut microbiota strategy for screening potential biomarkers associated with schizophrenia. (December 2022) - Gao, Yuhang; Liu, Xianglai; Pan, Mingyu; Zeng, Debin; Zhou, Xiying; Tsunoda, Makoto; Zhang, Yingxia; Xie, Xi; Wang, Rong; Hu, Wenting; Li, Lushuang; Yang, Haimei; et al.
Abstract: Schizophrenia (SZ) is a serious neurodevelopmental disorder. As the etiology of SZ is complex and the pathogenesis is not thoroughly understood, the diagnosis of different subtypes still depends on the subjective judgment of doctors. Therefore, there is an urgent need to develop early objective laboratory diagnostic biomarkers to screen different subtypes of patients as early as possible, and to implement targeted prevention and precision medicine to reduce the risk of SZ and improve patients' quality of life. In this study, untargeted metabolomics and 16 S rDNA sequencing were used to analyze the differences in metabolites and gut microflora among 28 patients with two types of schizophrenia and 11 healthy subjects. The results showed that the metabolome and sequencing data could effectively discriminate among paranoid schizophrenia patients, undifferentiated schizophrenia patients and healthy controls. We obtained 65 metabolites and 76 microorganisms with significant changes, and fecal metabolite composition was significantly correlated with the differential genera (|r|>0.5), indicating that there was a regulatory relationship between the gut microbiota and the host metabolites. The gut microbiome, as an objective and measurable index, showed good diagnostic value for distinguishing schizophrenia patients from healthy people, especially with a combination of several differential microorganisms, which had the best diagnostic effect (AUC>0.9). Our results are conducive to understanding the complicated metabolic changes in SZ patients and providing valuable information for the clinical diagnosis of SZ. Graphical abstract: Image 1